The Effect of Progressive Relaxation Techniques on Anxiety Levels in Schizophrenia Patients - Aisyah Nurul Fadhillah; Arif Widodo (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the mental disorders that can affect self-perception, emotions, behavior, and social functioning is schizophrenia. Schizophrenia patients may experience anxiety, behavioral disorders, cognitive disorders, speech disorders, and perception disorders. By calming the muscles of the head to the legs, progressive relaxation technique interventions are a nonpharmacological way to reduce anxiety. This study aims to determine the effect of the intervention of progressive relaxation techniques on the anxiety level of schizophrenia patients at RSJD Surakarta. The instrument used in this study was the Zung Self-Rating Anxiety Scale (ZSAS) on 30 respondents of schizophrenia patients who were surveyed and treated at RSJD Surakarta. A purposive sampling technique was used to determine the research objectives. The results showed that there was an effect of progressive relaxation technique intervention on the anxiety level of schizophrenia patients, using the Wilcoxon test with a significance result (p-value) = 0.001. In conclusion, the administration of progressive relaxation interventions in schizophrenia patients can have an effect in lowering the level of anxiety felt by patients.